Analysis of the Effect of Return on Equity, Capital Adequacy Ratio, and Loan to Deposit Ratio on Stock Prices - Yasa Astawa, I Kadek; Utama, I Made Karya (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Stocks have become an investment instrument that has been used by the public. One of the stocks that is in demand is the banking sector. The banking sector is considered to have the ability to survive all conditions because the banking sector is the driving force of the economy. To assess whether a bank's stock is in good condition, you can pay attention to its financial ratios such as Return of Equity (ROE), Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR). This study aims to obtain empirical evidence regarding the effect of ROE, CAR and LDR on stock prices. This study was conducted on banking companies listed in the Infobank15 index in the period 2020 to 2022. The sampling method used probability sampling and the SPSS application. The results of the study showed that Return of Equity had a positive and significant effect on banking stock prices. Then the results of the study on the effect of the Capital Adequacy Ratio also showed positive and significant results. However, the results of the Loan to Deposit Ratio study showed a negative and significant effect on banking stock prices. Then the size of the company as a control variable showed positive and significant results in controlling the effect of ROE, CAR and LDR on stock prices so as to avoid bias. The theoretical implication of this research is that it is able to support and add to the scientific treasury, especially signal theory. Meanwhile, the practical implication of this research is for investors and the public to pay more attention to banking financial ratios when considering investing in banking stocks.